A Case Report of 57 Year Old Male Having Post Fracture Stiffness of Right Shoulder with Supraspinatous Tear Case Report - Nikita Deshmukh; Vaidehi kannao; Waqar Naqv (Institute of Medico-legal Publications Pvt Ltd, 2021)
A case of lateral clavicle fracture associated with frozen shoulder is reported, which had reduced theabduction and lateral rotation due to frozen shoulder due to pain patient’s fear of being unable to do anyshoulder impact operation. MRI ruled out supraspinatous tear. Medical examination of the frozen shoulderconfirms the diagnosis. He was successfully treated with the combination of physical therapy treatmentwith the TENS, IFT, ultrasound and shoulder girdle mobilization electrotherapy modality. Scope of motioncomment per goniometer at 2, 4, 6, 8 weeks shoulder at. All the ranges are increased significantly.